Analisis Kesulitan Belajar Matematika pada Siswa Sekolah Dasar - Yatmi; Prasetyo, Krisno Budi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Students with math learning difficulties often make mistakes when learning to count and when trying to solve story problems. Students frequently experience difficulties when working on problems because they are not able to understand the meaning of the problem and become confused about using arithmetic operations. The purpose of this study is to identify the various kinds of numeracy learning challenges experienced by students, the factors that contribute to these challenges, and the strategies that can be used to overcome math learning challenges in grades IV and V of Sukosari Elementary School. This research method uses descriptive qualitative. The subjects of the study were 10 students in grades IV and V, as well as teachers in grades IV and V. The data collection procedures used were observation, interviews, test techniques and documentation. The results showed that there are several student learning difficulties such as understanding concepts, understanding mathematical language and numeracy skills are some of the challenges of learning mathematics. Furthermore, there are several factors that influence learning difficulties, namely internal and external factors. Students' attitudes and low interest in learning are the main causes of their learning challenges are internal factors. Lack of diversity in teachers' teaching, lack of utilization of learning resources, parents' concern, school infrastructure, and students' lack of sensory ability are examples of external influences that come from outside students. Keywords: Learning difficulties, elementary school students, mathematics